"30-minute-delta" of high-sensitivity troponin I improves diagnostic performance in acute myocardial infarction. Issue 2 (February 2018) - Yokoyama, Hiroaki; Higuma, Takumi; Endo, Tomohide; Nishizaki, Fumie; Hanada, Kenji; Yokota, Takashi; Yamada, Masahiro; Okumura, Ken; Tomita, Hirofumi
Highlights: Rapid and accurate diagnosis of acute myocardial infarction (AMI) are critical. Recently, a high-sensitivity cardiac troponin I (hs-cTnI) assay was developed. The diagnostic performance of "30-minute-delta" of hs-cTnI was evaluated. "30-minute-delta" of hs-cTnI presents improved diagnostic performance for AMI. Abstract: Background: Rapid and accurate diagnosis of acute myocardial infarction (AMI) are critical for the initiation of effective medical treatment. Recently, a high-sensitivity cardiac troponin I (hs-cTnI) assay was developed as a biochemical marker for the early diagnosis of AMI. Current guidelines recommend that serial measurements of cardiac troponin should be performed in patients who present symptoms suggestive of acute coronary syndrome. The aim of this study was to evaluate the diagnostic performance of 30-minute serial measurements of hs-cTnI for the detection of AMI. Methods: We prospectively enrolled patients presenting with suspected AMI within 12 h from symptom onset. We measured hs-cTnI levels at presentation and 30 min later to calculate the "30-minute-delta". The diagnostic performance was determined by the area under the receiver operating characteristic curve (AUC). Results: Among the 71 patients enrolled in this study, 55 (77%) were diagnosed with AMI. The hs-cTnI level at presentation was significantly greater in the patients with AMI than in those without AMI [306.2 (77.3–1809.9) pg/mL versus 22.5 (7.2–115.5) pg/mL, p  < 0.01]. The "30-minute-delta" was also significantly greater in patients with AMI [54.6 (13.5–288.0) pg/mL versus 1.9 (0.6–6.3) pg/mL, p  < 0.01]. The AUC of the "30-minute-delta" was significantly greater than that of a single measurement at presentation (0.911 versus 0.829, p  < 0.05). Conclusions: The "30-minute-delta" of hs-cTnI presents improved diagnostic performance for AMI compared with a single measurement.